Immunophenotype based on inflammatory cells, PD-1/PD-L1 signalling pathway and M2 macrophages predicts survival in gastric cancer - Junttila Anna; Helminen Olli; Väyrynen Juha P.; Ahtiainen Maarit; Kenessey Istvan; Jalkanen Sirpa; Mecklin Jukka-Pekka; Kellokumpu Ilmo; Kuopio Teijo; Böhm Jan; Mrena Johanna (NATURE PUBLISHING GROUP, 2022)
Background
Immune response against cancer has prognostic impact but its role in gastric cancer is poorly known. The aim of the study was to assess the prognostic significance of immune cell score (CD3+, CD8+), tumour immune escape (PD-L1, PD-1) and immune tolerance (Clever-1).
Methods
After exclusion of Epstein-Barr virus positive (n = 4) and microsatellite instable (n = 6) tumours, the study included 122 patients with GC undergoing D2 gastrectomy. CD3+ and CD8+ based ICS, PD-L1, PD-1 and Clever-1 expressions were evaluated. Differences in survival were examined using Cox regression adjusted for confounders. The primary outcome was 5-year survival.
Results
The 5-year overall survival rate was 43.4%. High ICS was associated with improved overall survival (adjusted HR 0.48 (95% CI 0.26-0.87)) compared to low ICS. In the high ICS group, patients with PD-L1 expression (5-year survival 69.2 vs. 53.1%, p = 0.317), high PD-1 (5-year survival 70.6 vs. 55.3% p = 0.312) and high Clever-1 (5-year survival 72.0% vs. 45.5% (p = 0.070) had poor prognosis.
Conclusions
High ICS was associated with improved survival. In the high ICS group, patients with high PD-L1, PD-1 and Clever-1 had poor prognosis highlighting the importance of immune escape and immune tolerance in GC.